2020
DOI: 10.3390/su12187812
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development, Institutional Quality, and Environmental Degradation Nexus: New Evidence from Asymmetric ARDL Co-Integration Approach

Abstract: The aim of this study is threefold; first, the study investigates the symmetric impact of trade openness, financial development, and institutional quality on environmental degradation and environmental sustainability. Second, the study examines the asymmetric relationship between financial development, institutional quality, and environmental degradation. Third, the study examines the asymmetric relationship between financial development, institutional quality, and environmental sustainability. For this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 39 publications
7
45
0
Order By: Relevance
“…According to United Nations Economic and Social Commission for Asia and Pacific (UNESCAP), in 2018, the Asia-Pacific region received a 45% share of global FDI inflows and it is also expected that this region will continue to serve as a major destination for FDI inflows in the upcoming years (Bhujabal et al 2021). Moreover, as the Asia-Pacific region is at a growing stage both economically and technologically, so FDI is considered a major channel of transfer of technology and hence affects the economic and environmental structure of the receiving countries (Ahmed et al 2020;Tang et al 2014). Therefore, developing countries should design policies to attract FDI and accelerate industrial progress but not at the expense of the environment and the health of their residents (Tang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to United Nations Economic and Social Commission for Asia and Pacific (UNESCAP), in 2018, the Asia-Pacific region received a 45% share of global FDI inflows and it is also expected that this region will continue to serve as a major destination for FDI inflows in the upcoming years (Bhujabal et al 2021). Moreover, as the Asia-Pacific region is at a growing stage both economically and technologically, so FDI is considered a major channel of transfer of technology and hence affects the economic and environmental structure of the receiving countries (Ahmed et al 2020;Tang et al 2014). Therefore, developing countries should design policies to attract FDI and accelerate industrial progress but not at the expense of the environment and the health of their residents (Tang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Second, after studying the literature, we concluded that the findings of prior researchers on the relation between GEP and environment are also conflicting, and the decisions of the prior researchers regarding the contributions of energy in ED and ES are based on the explicit measure of environment, i.e., CO 2 emissions. This study argues that when there is a separate measure for ES, we measure it with carbon emissions, Environmental Degradation (Ahmed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the study finds that "How does financial development contribute to environmental sustainability?" is still less focused on the available knowledge as only a few studies (Ahmed et al, 2020) explore the contributions of FD in EQ. Fourth, the study investigates the significant moderating role of CG in the affiliations between GEP, GIN, FD, and EQ with the help of solid theoretical supports.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling approach of ARDL was first pioneered by Pesaran, Shin, and Smith (1999) later in Pesaran, Shin, and Smith (2001) further extended this technique. This technique is considered as the most appropriate to use while working with small sample sizes (Ahmed, Kousar, Pervaiz, & Ramos-Requena, 2020). Many researchers have applied this co-integration technique to test long-run association among the variables for the case of small samples.…”
Section: Estimation Techniquesmentioning
confidence: 99%